Verdade em obra: arte e poesia na filosofia de Martin Heidegger - Fernandes, Larissa Sousa (2011)
This essay aims to understand how the thoughts about art and poetry are articulated in Martin Heidegger's (1889 1976) philosophy, by reading the lectures The origin of the work of art and Hölderlin and the essence of poetry. In Heidegger s work, art and poetry are analized totally separated from aesthetics appreciation and the literary critics, because the philosopher takes distance of dealing with art as a human Being's object of subjective appreciation. In Heidegger's fundamental ontology the work of art is seen in its own being. Allowing the work of art s Being a work of art, that it'll appear in its essence. The work of art, more than a subject of consideration, is seen here as a favored place where truth happens. The work of art is the place where truth happens, characterizing itself by not being covered. That happens because in the work of art a conflict between World and Earth. presents itself The world appears as an historical world, and the earth as the inhuman. in essence These are two opposing forces facing each other in a essential conflict in the work of art where one rises and shows up itself in the presence of the other. The truth appears in the strife of this conflict, essentially in the work of art. The truth as the uncovered being allows the being to show itself as it is. This way of unveiling the being is what the greeks called Téchne, an authentic production where the Being presents itself. Art is also found in the Téchne sphere, and the poetry, as the being s unveiled composition by the word, is, to Heidegger, a higher way of Téchne because it projects the human Being to the opening where is inlightment and concealment. By the poetic saying the being is named for the first time. Such naming is an unveiled say, which is only possible to be said by that ones hearing the Being, which are, according to Heidegger, the poets. They mediate an original relationship that long ago was lost, because they put themselves between the ones who waves the being's truth, the gods, and the ones to whom, for having a constituted language, these waves are accessible, the men. The poets are the guardians of these waves and have the mission of announcing them to an historical people, founding the poetic dwelling between men.